Enhanced load transfer by designing mechanical interfacial bonding in carbon nanotube reinforced aluminum composites. (May 2019) - Yu, Ziyun; Tan, Zhanqiu; Xu, Run; Ji, Gang; Fan, Genlian; Xiong, Ding-Bang; Guo, Qiang; Li, Zhiqiang; Zhang, Di
Abstract: The interfacial native oxide layer always acts as barriers preventing effective interfacial bonding and load transfer in carbon nanotube reinforced aluminum (CNT/Al) composites. In this work, annealing-controlled reaction between the interfacial native oxide layer and Mg element was attempted to improve interfacial bonding in CNT/AlMg composite, and mechanical interfacial bonding featured with direct CNT-Al contact and well-reserved CNTs was achieved in the 1 h annealed composite. For the 2 h annealed composite, chemical interfacial bonding featured with interfacial aluminum carbide (Al4 C3 ) was established due to progressive interfacial reaction. Further tensile tests and numerical analysis revealed that, owing to barrier-free load path and increased interfacial friction stress, the mechanical interfacial bonding significantly enhanced CNT load transfer effect from 30.9 MPa to 59.4 MPa, which was close to shear-lag model prediction of 59.9 MPa. While, the chemical interfacial bonding led to a combined strengthening effect of 58.8 MPa from CNT-Al4 C3 hybrid as a comprised outcome of Al4 C3 strengthening and CNT damage. Thus, the design of mechanical interfacial bonding should be a superior strategy for improving interfacial bonding and enhancing mechanical performance in CNT/Al composites, considering its effective protection of CNT structure integrity and suppressed formation of hydrolysable Al4 C3 phase. Graphical abstract: Image 1